Pengaruh Religiusitas dan Pengetahuan Produk Halal pada Minat Pembelian Produk E-commerce pada Mahasiswa UIN Jawa Timur - Moh Holilur Rohman; Lifia Lifia; Muhammad Haris Hidayatulloh (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Interest in buying in Indonesia is very important in the world of e-commerce every year increasing from 2017 there were 70.8 million to predictions for 2024 as many as 189.6 e-commerce users, this is not spared by students where the electronic world dominates, namely university students spread across Indonesia, 100% Islamic students are at UIN. The purpose of this study was to see halal labeling as mediation in buying interest in e-commerce products with religiosity and knowledge of halal products as variable Z by using the SmartPLS analysis tool. The results of this study show that the mediation aspect of halal labeling on religion has a full mediation effect, while halal labeling has a partial mediation effect on the interest in buying e-commerce products in UIN students in East Java. Meanwhile, religiosity has no effect on purchase intention with a t-statistic value of 1.430 <1.96 and a p-value of 0.153 > 0.05. on aspects of religiosity. Keywords: Religiosity, Knowledge of Halal Products, Purchase Intention.